Atypical Clinical Manifestations of Genital Herpes Simplex Virus Infection and Their Treatment - Garrido, Pedro Miguel (2018)
Genital herpes is a sexually transmitted infection with high global prevalence. Atypical clinical presentations of herpetic infection are rare but are becoming increasingly frequent due to the growing number of immunosuppressed patients. Therapy is challenging, with a longer treatment duration being frequently needed and an important resistance rate to the common anti-viral agents. Foscarnet and cidofovir are effective alternatives. In this article we review three atypical cutaneous presentations of herpetic infection, selected by their relevance in clinical practice: hypertrophic lesions, chronic ulcers and herpetic folliculitis.